Pengaruh Budaya Organisasi dan Lingkungan Kerja Fisik Terhadap Kepuasan Guru Di SMPN 3 Cimahi - Raden Annisa Thalia Destianta; Khaerul Rizal Abdurahman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Teacher satisfaction plays a major role in the development and education of students, including at SMPN 3 Cimahi. Students are more likely to be motivated to learn when their teachers are happy with their work because they tend to have more appropriate relationships with them. According to some experts, a positive workplace culture and physical surroundings can help people feel satisfied with their jobs. However, according to field observations, a number of teachers at SMPN 3 have not fully implemented the values ​​set, and there are still learning facilities that are less supportive. This study aims to analyze the extent to which organizational culture and physical work environment conditions affect the level of teacher job satisfaction at SMPN 3 Cimahi. By including all 52 teachers as respondents, this research employs a quantitative methodology. Questionnaires, observations, and interviews were used to gather data. Multiple regression analysis techniques processed with SPSS software accepted the quantitative descriptive and quantitative associative methods used in the data analysis process. The results of this investigation prove that organizational culture and work environment individually and together have a positive impact on teacher job satisfaction. This indicates that the consistent application of organizational cultural values, coupled with the existence of a conducive work environment, can significantly increase teacher satisfaction in carrying out their duties.